Using SnO2 QDs and CsMBr3 (M = Sn, Bi, Cu) QDs as Charge‐Transporting Materials for 10.6%‐Efficiency All‐Inorganic CsPbBr3 Perovskite Solar Cells with an Ultrahigh Open‐Circuit Voltage of 1.610 V. Issue 3 (8th January 2019) - Zhao, Yuanyuan; Duan, Jialong; Yuan, Haiwen; Wang, Yudi; Yang, Xiya; He, Benlin; Tang, Qunwei
Abstract : The power conversion efficiency (PCE) of state‐of‐the‐art perovskite solar cells (PSCs) with mesoscopic titanium dioxide (TiO2 ) has rushed to 23.7% in recent years. However, photodegradation of perovskites under illumination (including ultraviolet light), assisted by TiO2, significantly reduces the long‐term stability of the corresponding device, which in turn limits the commercialization of PSCs. Owing to the advantages of high electron mobility, wide bandgap, high transparency, and good photostability, nanostructured tin oxide (SnO2 ) is demonstrated to be a more promising electron‐transporting material for planar PSCs. Herein, low‐temperature solution‐processed SnO2 quantum dots (QDs) are employed as the electron transport layer (ETL) for all‐inorganic cesium lead bromide (CsPbBr3 ) PSC applications. Through optimizing the aging time of SnO2 QDs and adding a hole transport layer (HTL) of CsMBr3 (M = Sn, Bi, Cu) QDs between the CsPbBr3 layer and carbon electrode, the all‐inorganic PSC with a structure of FTO/SnO2 /CsPbBr3 /CsMBr3 /carbon achieves a good PCE of 10.60% with an ultrahigh open‐circuit voltage up to 1.610 V. These optimized devices, free of encapsulation, present excellent stability in 80% humidity or temperature of 80 °C. The maximized PCE report to date and improved environmental‐tolerance for all‐inorganic CsPbBr3 solar cells provide new opportunities to dramatically promote the commercialization of PSC platforms. Abstract : SnO2 QDs and CsMBr3 (M = Sn, Bi, Cu) QDs are applied as ETMs and HTMs for all‐inorganic CsPbBr3 PSCs, respectively. Arising from high optical transmittance and electron mobility of SnO2 QDs ETL as well as hole extraction of CsMBr3 QD HTL, the device achieves a good PCE of 10.60% and improved stability.